2009
DOI: 10.5216/ree.v11.47091
|View full text |Cite
|
Sign up to set email alerts
|

Risco ocupacional pela exposição ao glutaraldeído em trabalhadores de serviços de endoscopia

Abstract: O glutaraldeído, amplamente utilizado no reprocessamento de endoscópios pelas vantagens e baixo custo, apresenta alta toxicidade e pode expor os profissionais a riscos ocupacionais. Pesquisa descritiva realizada em 2007 em serviços de endoscopia digestiva de Goiânia-GO/Brasil que caracterizou por meio de um questionário e observação direta registradas em check list, a exposição ocupacional dos profissionais que reprocessam endoscópios, verificando as manifestações clínicas relatadas por eles e a ventilação do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…However, it was found that there is a decline after some training time, emphasizing the need for training on a systematic and periodic basis. 12 It was also observed in another study that professionals do not fully adhere to standard precautions as recommended, although standard precautions are the main strategy for protecting workers from exposure to transmissible pathogens 12 and, like the patient, adherence is below recommended. They stand out as factors that contribute to low adherence: lack of knowledge; lack of training; time; habit; forgetfulness; lack of PPE; impact on technical skill; uncomfortable equipment; skin irritation; conflict between the need to provide care and self-protection; distance between PPE and place of use.…”
Section: Methods Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that there is a decline after some training time, emphasizing the need for training on a systematic and periodic basis. 12 It was also observed in another study that professionals do not fully adhere to standard precautions as recommended, although standard precautions are the main strategy for protecting workers from exposure to transmissible pathogens 12 and, like the patient, adherence is below recommended. They stand out as factors that contribute to low adherence: lack of knowledge; lack of training; time; habit; forgetfulness; lack of PPE; impact on technical skill; uncomfortable equipment; skin irritation; conflict between the need to provide care and self-protection; distance between PPE and place of use.…”
Section: Methods Resultsmentioning
confidence: 99%
“…It should be added that the use of PPE -gloves, apron, masks and eye protectors -must also observe hand hygiene before and after contact with the patient and body fluids. 12 It is known that occupational diseases affect productivity, quality and health of workers and there are several causes of accidents, such as carelessness, patient conditions, failure to observe preventive measures, inadequate materials, equipment and structure, haste, risk inherent to the profession, overconfidence and work overload. It is observed that, if basic protection measures were adopted, many accidents could be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Dados semelhantes, quanto à exposição ocupacional pela deficiência na aeração, na área de reprocessamento de artigos em glutaraldeído, foi observado por pesquisas (17)(18) em Goiânia, que também identificaram também a exposição dos profissionais ao produto e alto índice de sinais clínicos relacionados à atividade laboral.…”
Section: Discussionunclassified
“…Qualquer superfície, inclusive as da SO, deveria ser isenta de micro-organismos, no entanto, a transferência desses agentes a esses locais comumente ocorre por respingos de fluídos envolvidos no procedimento cirúrgico e pelas mãos dos profissionais de saúde (4)(5) , Individual (EPI), a fim de minimizar os riscos ocupacionais, biológico e químico (1,(5)(6) .…”
Section: Introductionunclassified